Joint source-channel coding - Kwasinski, Andres; Chande, Vinay (Hoboken: John Wiley & Sons., 2023)
"Presenting in one volume the key theories, concepts and important developments in the area of Joint Source-Channel Coding (JSCC), this book provides the fundamental material needed to enhance the performance of digital and wireless communication systems and networks. It comprehensively introduces the joint source-channel coding technologies for communications systems, including the coding and decoding algorithms, and its emerging applications in current wireless communications. Beginning with introductory material on the topic, the content also covers the full range of theoretical and technical areas before concluding with a section considering emerging applications and designs for source-channel coding"--
Includes bibliographical references and index.
Keywords: Combined source channel coding